THE EFFECT OF USING STORYTELLING TECHNIQUE IN TEACHING GRAMMAR FOR EFL CLASSROOM : (An Experiment study at STKIP BinaBangsaGetsempena Banda Aceh) - Siti Fachraini (English Education Department, 2016)
This study is intended to find out the effect of using storytelling to increase students’ ability in mastering grammatical structure focused on past tense subject and to investigate if there any significance differences in students’ score between students taught by using storytelling technique and traditional method. Research method used in this study was experimental study in which the participants were students of STKIP BinaBangsaGetsempena Banda Aceh. They were EFL students who studied at Pendidikan Guru SekolahDasar (PGSD) department. The students were 50 students divided into two groups (experimental class and control class). The instrument used was tests (pre-test and post-test) which were given before and after treatment. Experimental group was taught by using storytelling technique otherwise control group was taught by using traditional method. The result of the study shows that tobtain>ttable that is 5.139 > 2.00, so H0 is rejected. In other words, the students who were taught using storytelling technique achieved a better ability in mastering grammatical structure than the students who were taught grammar by using traditional method.It indicates that there is a significant differences in the experimental group compared to the control group. Thus, it can be concluded that storytelling technique is effective in increasing students’ ability in mastering grammar.